Identification of residues involved in the specificity and regulation of the highly efficient multisubstrate deoxyribonucleoside kinase from Drosophila melanogaster. - Knecht, W.; Munch-Petersen, B.; Piskur, J. (Journal of Molecular Biology, 2000)
In contrast to all known deoxyribonucleoside kinases, a single highly efficient deoxyribonucleoside kinase from Drosophila melanogaster (Dm-dNK) is able to phosphorylate all precursor nucleosides for DNA synthesis. Dm-dNK was mutated in vitro by high-frequency random mutagenesis, expressed in the thymidine kinase-deficient Escherichia coli strain KY895 and clones were selected for sensitivity to the nucleoside analogs 1-beta-d-arabinofuranosylcytosine (AraC, Cytarabine), 3'-azido-2', 3'-dideoxythymidine (AZT, Zidovudine, Retrovir, 2', 3'-dideoxyadenosine (ddA) and 2',3'-dideoxycytidine (ddC, Zalcitabine, Hivid. Thirteen mutants with increased sensitivity compared to the wild-type Dm-dNK were isolated from a relatively small pool of less than 10,000 clones. Eight mutant Dm-dNKs increased the sensitivity of KY895 to more than one analog, and two of these mutants even to all four nucleoside analogs. Surprisingly, the mutations did not map to the five regions which are highly conserved among deoxyribonucleoside kinases. The molecular background of improved sensitivity was characterized for the double-mutant MuD (N45D, N64D), where the LD(100) value of transformed KY895 decreased 316-fold for AZT and more than 11-fold for ddC when compared to wild-type Dm-dNK. Purified recombinant MuD displayed higher K(m) values for the native substrates than wild-type Dm-dNK and the V(max) values were substantially lower. On the other hand, the K(m) and V(max) values for AZT and the K(m) value for ddC were nearly unchanged between MuD and wild-type Dm-dNK. Additionally, a decrease in feedback inhibition of MuD by thymidine triphosphate (TTP) was found. This study demonstrates how high-frequency mutagenesis combined with a parallel selection for desired properties provides an insight into the structure-function relationships of the multisubstrate kinase from D. melanogaster. At the same time these mutant enzymes exhibit properties useful in biotechnological and medical applications.